Cultural politics in Polybius's Histories - Champion, Craige Brian (University of California Press, 2004)
Polybius has provided us with the earliest continuous narrative of the rise of the Roman Empire. Champion shows how Polybius tailored his work for a number of audiences, both his fellow Greeks & the Roman conquerors, affording new insights into a work whose subtlety & complexity have gone largely unrecognised.
Keywords: Polybius. -- Historiae.; Polybe. -- Histoires.; Historiae (Polybius); Polybius -- v200-v120 -- Historiae; De excidio urbis Hierosolymitanae; Polybius.; History, Ancient -- Historiography.; Civilization, Classical -- Historiography.; Rome -- Politics and government -- 265-30 B.C. -- Historiography.; Greece -- Politics and government -- To 146 B.C. -- Historiography.; Histoire ancienne -- Historiographie.; Civilisation ancienne -- Historiographie.; Rome -- Politique et gouvernement -- 265-30 av. J.-C. -- Historiographie.; Grèce -- Politique et gouvernement -- Jusqu'à 146 av. J.-C. -- Historiographie.; HISTORY -- Ancient.; HISTORY -- Ancient -- General.; Civilization, Classical -- Historiography; History, Ancient -- Historiography; Politics and government -- Historiography; Greece; Rome (Empire); Kulturelle Identität; Römerbild; Römisches Reich; Culturele identiteit.; Politieke aspecten.; Griechen.; To 30 B.C.